(untitled) (Journal of Applied Learning and Teaching, 2021)
The Covid-19 pandemic disrupted our world on a major scale in 2020 and will continue to be part of our lives for some time to come. This paper examines how students in the Murina Program were supported by the Aboriginal and Torres Strait Islander Education Unit, the ‘Riawunna Centre’ at the University of Tasmania (UTAS), to help overcome the challenges of Covid-19 in 2020. It explores enrolment data, feedback and work samples provided by students about the ways in which Riawunna supported them to successfully transition to online learning and continue to meet unit level learning outcomes 2020. Data were collected in early 2021 and all ethical requirements for publication were met. The analysis of formal institutional level student feedback surveys suggest that Murina students highly valued the support provided by all Riawunna staff during the pandemic as highly critical to their engagement with Aboriginal pedagogy, through the sharing of Aboriginal knowledges and yarns within a curriculum that strengthened connections during this very challenging period. Ongoing research in this space will continue to investigate the impact of the Murina Program pedagogy to give students voice and agency to redefine their definition of success.